A Phenomenological Actor - Kirkkopelto, Esa (University of Alberta, 2022)
In this article, I will open my artistic research process from the phenomenological point of view, by aiming at identifying its phenomenological aspects and potential. My presentation will proceed as a series of practical demonstrations, which enable us to perceive how an actor as a scenic performer conceives their corporeal practice and what kind of phenomena they produce, encounter and operates with. The experience and idea of corporality, rising from the scenic practices described, set new kind of challenges to the phenomenology of embodiment.
Keywords: fenomenologia; taiteellinen tutkimus; taidefilosofia